Total colonic aganglionosis and imperforate anus in a severely affected infant with Pallister‐Hall syndrome. (21st January 2015) - Li, Mindy H.; Eberhard, Moriah; Mudd, Pamela; Javia, Luv; Zimmerman, Robert; Khalek, Nahla; Zackai, Elaine H.
<x xml:space="preserve">Abstract</x> Pallister‐Hall syndrome is a complex malformation syndrome characterized by a wide range of anomalies including hypothalamic hamartoma, polydactyly, bifid epiglottis, and genitourinary abnormalities. It is usually caused by truncating frameshift/nonsense and splicing mutations in the middle third of GLI3. The clinical course ranges from mild to lethal in the neonatal period. We present the first patient with Pallister‐Hall syndrome reported with total colonic aganglionosis, a rare form of Hirschsprung disease with poor long‐term outcome. The patient also had an imperforate anus, which is the third individual with Pallister‐Hall syndrome reported with both Hirschsprung disease and an imperforate anus. Molecular testing via amniocentesis showed an apparently de novo novel nonsense mutation c.2641 C>T (p.Gln881*). His overall medical course was difficult and was complicated by respiratory failure and pan‐hypopituitarism. Invasive care was ultimately withdrawn, and the patient expired at three months of age. This patient's phenotype was complex with unusual gastrointestinal features ultimately leading to a unfavorable prognosis and outcome, highlighting the range of clinical severity in patients with Pallister‐Hall syndrome. © 2015 Wiley Periodicals, Inc.